Online couples mindfulness-based intervention for young breast cancer survivors and their partners: A randomized-control trial. Issue 5 (2nd September 2020) - Price-Blackshear, Mollie A.; Pratscher, Steven D.; Oyler, Danielle L.; Armer, Jane M.; Cheng, An-Lin; Cheng, Maggie X.; Records, Kathie; Udmuangpia, Tipparat; Carson, James W.; Ann Bettencourt, B.
Abstract: Purpose: Young breast cancer survivors (YBCS) face unique challenges in coping with disease, distress, and relationship concerns. The purposes of this study were to understand the acceptability and feasibility of an online Mindfulness-Based Intervention (MBI) for YBCS and their partners (i.e., Couples Mindfulness-Based Intervention: C-MBI) and to compare the effectiveness of the C-MBI to a closely-matched control, an online MBI for individuals (I-MBI). Methods: YBCS and their partners were recruited. Couples were randomly assigned to an 8-week C-MBI (couples = 41) or to I-MBI (couples = 36), which included one-hour video modules, a manual, and guided-meditation audios. Both couple members participated in the C-MBI; only the YBCS participated in the control I-MBI. Participants answered surveys about individual- and couple-level functioning at baseline and post-intervention. Results: Online delivery was shown to be feasible and acceptable. For YBCS and their partners, levels of perceived stress, anxiety, depression, and fatigue were lower after the intervention, in both conditions. Unexpectedly, however, participating in the C-MBI appeared to have detrimental effects on dyadic adjustment and relationship quality. Conclusion: Although YBCS and their partners reported online delivery was acceptable and benefited well-being, for couple-based MBIs to have benefits for relationship functioning, it may be necessary for couples to have the support of other couples and an instructor. Online delivery may be particularly acceptable and effective for clinical populations, including YBCS. Medical professionals may be more likely to recommend online-MBI programs to cancer survivors, because the programs are of little or no cost.